GENETIC VARIABILITY STUDIES FOR YIELD AND ITS ATTRIBUTES, QUALITY AND NUTRITIONAL TRAITS IN MEDIUM DURATION RICE GENOTYPES (Oryza sativa L.): GENETIC VARIABILITY STUDIES IN MEDIUM DURATION RICE GENOTYPES (ORYZA SATIVA L.) - V. MADHUSUDHAN REDDY; Y. SUNEETHA; C. N. NEERAJA (The Journal of Research ANGRAU, 2026)
The experiment was conducted during kharif, 2024 at Regional Agricultural Research Station, Maruteru. Sixty-four genotypes of medium duration rice (Oryza sativa L.) were evaluated for genetic variability, heritability and genetic advance as per cent of mean for 15 quantitative traits. Analysis of variance revealed significant differences for all the characters under study. High genotypic coefficient of variation (GCV) 21.000% and phenotypic coefficient of variation (PCV) 20.642% were observed for the character viz.,grains per panicle. High heritability coupled with high genetic advance as percent mean was observed for grains per panicle, no of grains per cm panicle, grain density, test weight, grain yield per plant and high protein content indicating the effectiveness of simple selection in improvement of these traits.